2022
DOI: 10.1186/s42408-022-00133-8
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment characteristics and early regeneration after the 2018 Spring Creek Wildfire and post-fire logging in Colorado, USA

Abstract: Background Wildfires are increasing in size and severity in forests of the western USA, driven by climate change and land management practices during the 20th century. Altered fire regimes have resulted in a greater need for knowledge on best practices for managing burned landscapes, especially in instances where a return to a previous forested ecosystem is desired. We examined a large wildfire from 2018 in southern Colorado to understand how fire severity and post-fire logging influenced stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
5
0
1
Order By: Relevance
“…These studies, combined with other results from clear-cutting and salvage-logging operations [13,19,25,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], indicate a wide variety of responses in soil temperatures and moisture depending on site-specific circumstances. In our mixed conifer forests of northern New Mexico, the retention of natural logs following thinning and burning provided microsites with generally warmer sub-log soil temperatures in spring, summer, and fall, while adjacent sites experienced comparable warming levels.…”
Section: Discussionmentioning
confidence: 77%
“…These studies, combined with other results from clear-cutting and salvage-logging operations [13,19,25,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], indicate a wide variety of responses in soil temperatures and moisture depending on site-specific circumstances. In our mixed conifer forests of northern New Mexico, the retention of natural logs following thinning and burning provided microsites with generally warmer sub-log soil temperatures in spring, summer, and fall, while adjacent sites experienced comparable warming levels.…”
Section: Discussionmentioning
confidence: 77%
“…Milleroń et al (2013) found large disparities between seed dispersal kernels and kernels from established saplings, suggesting that dispersal alone is insufficient to capture patterns in recruitment and survival. Although we attempted to include variables that might distinguish between site quality and thus the probability of seedling establishment, we simply could not precisely determine the effects of site quality (i.e., soil moisture or temperature, see Wooten et al, 2022) with our data. For example, the presence of downed logs and shrubs can provide protection and increase soil moisture for regenerating seedlings (Tappeiner and Helms, 1971;Landesmann and Morales, 2018;Marcolin et al, 2019).…”
Section: Limitationsmentioning
confidence: 99%
“…Fire-tolerant plant species generally increased in abundance at the expense of those killed by fire (fire-sensitive plants) due to a considerable reduction in competition and possibly due to alternations in other conditions (Gallagher et al, 2022). Regeneration of post-fire trees depends on a variety of factors, from climate suitability to the characteristics of the microsite (Wooten et al, 2022). A successful reestablishment post-fire may be influenced by seed source, climate, competition or facilitation, and micro-climates (Stevens-Rumann and Morgan, 2019).…”
Section: Introductionmentioning
confidence: 99%